The Importance of Non-Governmental Organizations in Contemporary Governance at Local Level - Pavlova, Petia (Research Papers, 2018)
In this article, the author tries to analyze the interaction between local government and the non-governmental sector. The paper presents the good practice for joint work between Municipality of Sozopol and SOZOPOL Foundation. Various projects of cultural, historical, tourist and social character, realized by the Foundation on the territory of Sozopol, and the results of their impact on the life of the local population and the development are presented.